Quantifying 210Po/210Pb Disequilibrium in Seawater: A Comparison of Two Precipitation Methods With Differing Results - Roca-Martí, Montserrat; Puigcorbé, Viena; Castrillejo, Maxi; Casacuberta, Núria; Garcia-Orellana, Jordi; Cochran, J. Kirk; Masqué, Pere (Frontiers in Marine Science, 2021)
The disequilibrium between lead-210 (210Pb) and polonium-210 (210Po) is increasingly used in oceanography to quantify particulate organic carbon (POC) export from the upper ocean. This proxy is based on the deficits of 210Po typically observed in the upper water column due to the preferential removal of 210Po relative to 210Pb by sinking particles. Yet, a number of studies have reported unexpected large 210Po deficits in the deep ocean indicating scavenging of 210Po despite its radioactive mean life of ∼ 200 days. Two precipitation methods, Fe(OH)3 and Co-APDC, are typically used to concentrate Pb and Po from seawater samples, and deep 210Po deficits raise the question whether this feature is biogeochemically consistent or there is a methodological issue. Here, we present a compilation of 210Pb and 210Po studies that suggests that 210Po deficits at depths >300 m are more often observed in studies where Fe(OH)3 is used to precipitate Pb and Po from seawater, than in those using Co-APDC (in 68 versus 33% of the profiles analyzed for each method, respectively). In order to test whether 210Po/210Pb disequilibrium can be partly related to a methodological artifact, we directly compared the total activities of 210Pb and 210Po in four duplicate ocean depth-profiles determined by using Fe(OH)3 and Co-APDC on unfiltered seawater samples. While both methods produced the same 210Pb activities, results from the Co-APDC method showed equilibrium between 210Pb and 210Po below 100 m, whereas the Fe(OH)3 method resulted in activities of 210Po significantly lower than 210Pb throughout the entire water column. These results show that 210Po deficits in deep waters, but also in the upper ocean, may be greater when calculated using a commonly used Fe(OH)3 protocol. This finding has potential implications for the use of the 210Po/210Pb pair as a tracer of particle export in the oceans because 210Po (and thus POC) fluxes calculated using Fe(OH)3 on unfiltered seawater samples may be overestimated. Recommendations for future research are provided based on the possible reasons for the discrepancy in 210Po activities between both analytical methods.